Juventudes camponesas: práticas e vivências agroecológicas no território da Borborema - Silva, Luana Patricia Costa (2019)
The aim of this doctoral thesis is to analyze the possibilities developed by the youth from the Borborema Territory, based on the participation of these subjects in the Course on Agrarian Residence, offered by the National Program of Education on Agrarian Reform (PRONERA). The course is part of the extension program offered by the Federal University of Paraíba in partnership with the Brazilian National Research Council (CNPq). The present research results from a field work and follows a qualitative approach. The Participant Research is the central methodological base of the study; following this base, we focus our practice on participant observation and oral stories, drawing on references that supported the theoretical and empirical study and underpinned the analysis through the dialogue with theoretical discussions directed to Territory, Rural Education and Agroecology. Approximately 60 young peasants, distributed in two classes, attended the course between 2015 and 2017. Thus, space and subjects formed the empirical territory of this doctoral thesis, with a greater emphasis on the subjects following a geographic/territorial focus. We investigated the space of the Territory and the organizational trajectory of the young people present in the Borborema Territory, as well as followed their daily processes during and after the formation in the Agrarian Residence, elucidating the possible relations with practices directed to the dialogue with Agroecology. This research enabled an approximation to the historical and resistance context of the Agroecological Territory of Borborema, as well as an understanding of the role of the young peasants in their organizational processes. It still pointed to elements of the distinct formations of those young people, between distances and approaches to their peasant identities, which were understood through the narratives and experiences in the field of the research. The elements found in the results goes from past to present memories that construct and re-signify these identities, explain and give life to the plans by the youth in a present time, giving possibilities to the permanence in the countryside, through the articulation and organization of this political category: the peasant youths.